Metal-free, in bulk synthesis of highly hydrophilic polyester bearing pyrrolidone pendants and its diblock copolymers with UCST-type phase transition in water. (15th February 2022) - Li, Huanting; Liang, Xingran; Zhang, Yuan; Yan, Yuhua; Lin, Jingjing; Li, Minfeng
Graphical abstract: Highlights: Well defined polyester obtained via controlled solvent-free organocatalytic ROP of δ-valerolactone (pyvl) functionalized with pyrrolidone (Py) pendants exhibits high hydrophiliicity and hydrolytical labilility. Its diblock co-polyesters with ε-caprolactone (CL), poly(pyvl)20 - b -PCL60, exhibits sharp and concentration-independent UCST type phase transition at around 35 °C in pure water. Abstract: Aliphatic polyesters are readily degradable, highly hydrophobic and lack of functionality. In contrast, polyvinylpyrrolidone (PVP), a vinyl-based polymer, exhibits excellent water solubility owning to its highly hydrophilic pyrrolidone (Py) pendant groups but suffers from degradation issues due to stable C-C bonds in its backbones. Functionalizing polyester with pyrrolidone pendant groups leads to a new type of polymer that is highly hydrophilic and hydrolytically labile at the same time. Well defined functional polyesters can be obtained via controlled ring opening polymerization (ROP) of functional lactone monomers. Functionalization of δ-valerolactone with Py groups is realized by thiol-ene click ligation and subsequent oxidation to afford functional lactone (pyvl). Bulky pendant groups, Py, on lactone rings impede ROP of the functionalized lactones. It is found that strong Brønsted superacid, trifluoromethanesulfonic acid (HOTf), can promote bulk ROP of pyvl at 120 °C and that control of the polymerization can be moderately improved in the presence of diphenylphosphate (DPP) under these conditions. Well defined functional polyesters, poly(pyvl)s, are found to be highly hydrophilic and hydrolytically labile. Surprisingly, its amphiphilic block copolymers such as poly(pyvl)20 - b -PCL60 exhibit sharp and concentration-independent UCST type phase transition at around 35 °C in pure water.